Morpho-hydraulic parameters and existing stability condition of Nakhu River, southern Kathmandu, Central Nepal - Maharjan, Binod; Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2010)
DOI: 10.3126/bdg.v13i0.3961 Bulletin of the Department of Geology Vol.13 2010, pp.1-12